2001
DOI: 10.1542/peds.108.3.e48
|View full text |Cite
|
Sign up to set email alerts
|

Montelukast, a Leukotriene Receptor Antagonist, for the Treatment of Persistent Asthma in Children Aged 2 to 5 Years

Abstract: ABSTRACT. Background. The greatest prevalence of asthma is in preschool children; however, the clinical utility of asthma therapy for this age group is limited by a narrow therapeutic index, long-term tolerability, and frequency and/or difficulty of administration. Inhaled corticosteroids and inhaled cromolyn are the most commonly prescribed controller therapies for young children with persistent asthma, although very young patients may have difficulty using inhalers, and dose delivery can be variable. Moreove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
211
1
22

Year Published

2002
2002
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 343 publications
(239 citation statements)
references
References 34 publications
5
211
1
22
Order By: Relevance
“…Montelukast is an orally bioavailable cysteinyl leukotriene (LT) receptor antagonist that is effective, safe, well tolerated, and approved by the U.S. Food and Drug Administration for preventive therapy for the inflammatory component in asthma and allergic rhinitis in children 2 years and older (21)(22)(23)(24), with no demonstrable development of tolerance in long-term studies (25,26). We have recently found that the cloned human cysteinyl LT receptors 1 and 2 (LT1-R, LT2-R) (27,28) have increased expression in the tonsillar tissues of children with SA (29).…”
mentioning
confidence: 99%
“…Montelukast is an orally bioavailable cysteinyl leukotriene (LT) receptor antagonist that is effective, safe, well tolerated, and approved by the U.S. Food and Drug Administration for preventive therapy for the inflammatory component in asthma and allergic rhinitis in children 2 years and older (21)(22)(23)(24), with no demonstrable development of tolerance in long-term studies (25,26). We have recently found that the cloned human cysteinyl LT receptors 1 and 2 (LT1-R, LT2-R) (27,28) have increased expression in the tonsillar tissues of children with SA (29).…”
mentioning
confidence: 99%
“…26 Spahn et al 17 have recently confirmed the effects of montelukast on peripheral airway obstruction and the concentration of eosinophilic cationic protein in children and adolescents with moderate asthma.…”
Section: Leukotrienes In Asthmamentioning
confidence: 90%
“…A 12-week, multicentre, randomized, placebo-controlled, double-blind, parallel-group study was conducted to evaluate the clinical safety and efficacy of oral montelukast in 689 children 2 to 5 years of age with chronic asthma. 11 Montelukast significantly improved each of the components of the composite symptom score over 12 weeks of treatment. For example reduction in activity limitation scores were 40% versus 22% (p<0.001).…”
Section: Leukotriene Receptor Antagonistsmentioning
confidence: 90%
“…11 There improved compliance and safety make these agents seem attractive as alternatives for ICS in young children with mild persistent asthma. They also provide an alternative to long-acting β 2 -agonists as add on therapy.…”
Section: Leukotriene Receptor Antagonistsmentioning
confidence: 99%